INFLATION CONVERGENCE IN NEW EMU MEMBERS - Popović, Svetlana (Ekonomija - teorija i praksa, 2022)
The European Central Bank is responsible for managing the common monetary policy for 19 countries that are geographically and economically very heterogeneous. The question is whether the common monetary policy suits all of them. We focused on countries that joined the Monetary union since 2007 (new members), to understand if they managed to "fit in". Those countries made impressive progress in macroeconomic and price stability, but is it enough to simply enjoy net benefits from EMU membership? After analyzing statistical characteristics of their inflation processes since 1997 (mean and median inflation, standard deviation and coefficient of variations), we wanted to understand if their inflation rates have converged towards EMU average inflation rate and if they tend to form a more homogeneous group of countries. We conducted a unit root test to statistically check the significance of the convergence process, and analyzed autocorrelation coefficients of inflation rates to assess the influence of the common monetary policy on the persistence of inflation. The results did not statistically confirm the existence of absolute convergence of inflation rates in New EMU members.